Brief Report: Drop in CD4+ Counts Below 200 Cells/μL After Reaching (or Starting From) Values Higher than 350 Cells/μL in HIV-Infected Patients With Virological Suppression. (1st December 2017) - Gianotti, Nicola; Marchetti, Giulia; Antinori, Andrea; Saracino, Annalisa; Gori, Andrea; Rizzardini, Giuliano; Lichtner, Miriam; Bandera, Alessandra; Mussini, Cristina; Girardi, Enrico; d'Arminio Monforte, Antonella; Cozzi-Lepri, Alessandro
Abstract : Background: The aim of the study was to quantify the risk of a drop in CD4 + counts below 200 cells/μL after reaching values >350 cells/μL on antiretroviral therapy (ART) (or after starting ART with CD4 + count >350 cells/μL) in the absence of virological failure. Setting: Ambulatory care services, Italy. Methods: Prospective cohort study of patients enrolled in the ICONA Foundation Study cohort who started ART with >350 CD4 + /μL or with ⩽350 CD4 + /μL and reached values >350 cells/μL after virological suppression (VS, defined by 2 consecutive viral loads ⩽50 copies/mL). The date of CD4 count >350 was the baseline for the analysis and those with ≥1 viral load and CD4 + count after baseline were included. The primary end point was the cumulative risk (estimated using the Kaplan–Meier method) of a CD4 + drop below 200 cells/μL over follow-up, which was censored at the date of virological failure (confirmed HIV-RNA >50 copies/mL), death, or last visit. Results: Six thousand six hundred sixty-three patients were included. A confirmed CD4 + drop below 200 cells/μL was never observed over a median follow-up of 45 (Q1: 21, Q3: 89) months, as long as VS was maintained. Upper limits of the 97.5% confidence interval of rates of confirmed CD4 + drop below 200 cells/μL were 0.28 and 0.38/1000 person-years of follow-up for patients with ⩽350 and >350 CD4 + cells/μL at starting ART. Conclusions: In patients who started ART in Italy with >350 CD4 + cells/μL or reached >350 CD4 + cells/μL after VS, the risk of a CD4 + drop below 200 cells/μL in those maintaining VS was negligible. Abstract : Supplemental Digital Content is Available in the Text.